Desenvolvimento de aplicativo para identificação de artrópodes como recurso na aprendizagem de taxonomia a estudantes do ensino médio - Rosa Filho, Dicler Costa (2020)
Mobile phones are present in people's daily lives, and consequently in schools. Therefore, it can be an excellent resource to facilitate learning. This work aimed to build and develop an app for smartphones together with high school students to help in the identification of arthropods. Given the degree of complexity of the technical terms used in taxonomy, the concepts may not make much sense to students, making learning difficult. Using an illustrated resource and with an easy to understand language this content can make more sense for the student. The product was positively evaluated by students and teachers, mainly for its simplicity of use and the low cost of the product, since the application is free and only requires space in the memory of the mobile phone and the internet to download it. Also, we can obse